Rezistence k makrolidůim u druhu Streptococcus pyogenes v Ceské republice v období let 1996-2003 - Urbásková, P; Jakubů, V; Pracovní skupina pro monitorování antibiotické rezistence (Epidemiologie, mikrobiologie, imunologie, 2004)
The study of the prevalence of erythromycin resistance in 22 169 S. pyogenes strains in the Czech Republic in 1996-2003 on the background of rough data on the nationwide consumption of macrolide antibiotics confirmed that the exponential growth of resistance observed in 1998-2001 copied with a delay the rise in macrolide antibiotic consumption recorded in 1992-1995. The highest frequency of erythromycin resistance was found in 2001 (16.5%) with a subsequent decrease to 14.5% in 2002 and to 9.1% in 2003. The drop in resistance followed the stagnation in macrolide consumption and its decrease by 17% in 2002. Upward and downward trends in macrolide resistance in different regions and age groups copied the nationwide trends with some quantitative differences that could not be analyzed in view of the lack of detailed data on antibiotic consumption. A 99.5% concordance was found between the results of the phenotypic method and those of detection of genes coding for constitutive, inducible and efflux resistance to macrolide-lincosamide-streptograminB (MLSB) antibiotics. In 2001 when the highest erythromycin resistance was recorded in the Czech Republic, most of the tested strains (91.2%) showed resistance to all MLSB antibiotics, with macrolide efflux (susceptibility to lincosamides and 16-membered macrolides was conserved) being implicated in resistance of 8.8% of the strains only. In 2003, the number of erythromycin resistant strains decreased and the resistance mechanism was ascribed to macrolide efflux in 26.8% of them. Almost all of the strains with constitutive or induced MLSB resistance are also resistant to either tetracycline or bacitracin or both. In the light of S. pyogenes resistance to bacitracin, the bacitracin disk is not usable in preliminary identification any more.
Keywords: dospělí; dítě; předškolní dítě; streptokokové infekce; Adult; Macrolides; Adolescent; lidé; makrolidy; erythromycin; bakteriální léková rezistence; Streptococcus pyogenes; Erythromycin; Streptococcal Infections; Child, Preschool; Child; Drug Resistance, Bacterial; mladiství; Humans